Analysis And Evaluation Of The Budgeting System: A Study Of Jamsaz Industrial Production Co. - Bybordi, Nazanin (2010)
The current study is an analysis of current budgeting system of Jamsaz Industrial Production Co., an Iranian manufacturing firm specializing automotive lighting, in terms of planning, operation, and to highlight some major causes of budget variances. Also,this study aims to suggest effective ways to minimize such variances by analyzing the company\'s budgeting system.